Evaluating Interaction of Cord Blood Hematopoietic Stem/Progenitor Cells with Functionally Integrated Three-Dimensional Microenvironments. (23rd February 2018) - Mokhtari, Saloomeh; Baptista, Pedro M.; Vyas, Dipen A.; Freeman, Charles Jordan; Moran, Emma; Brovold, Matthew; Llamazares, Guillermo A.; Lamar, Zanneta; Porada, Christopher D.; Soker, Shay; Almeida-Porada, Graça
Abstract : Despite advances in ex vivo expansion of cord blood-derived hematopoietic stem/progenitor cells (CB-HSPC), challenges still remain regarding the ability to obtain, from a single unit, sufficient numbers of cells to treat an adolescent or adult patient. We and others have shown that CB-HSPC can be expanded ex vivo in two-dimensional (2D) cultures, but the absolute percentage of the more primitive stem cells decreases with time. During development, the fetal liver is the main site of HSPC expansion. Therefore, here we investigated, in vitro, the outcome of interactions of primitive HSPC with surrogate fetal liver environments. We compared bioengineered liver constructs made from a natural three-dimensional-liver-extracellular-matrix (3D-ECM) seeded with hepatoblasts, fetal liver-derived (LvSt), or bone marrow-derived stromal cells, to their respective 2D culture counterparts. We showed that the inclusion of cellular components within the 3D-ECM scaffolds was necessary for maintenance of HSPC viability in culture, and that irrespective of the microenvironment used, the 3D-ECM structures led to the maintenance of a more primitive subpopulation of HSPC, as determined by flow cytometry and colony forming assays. In addition, we showed that the timing and extent of expansion depends upon the biological component used, with LvSt providing the optimal balance between preservation of primitive CB HSPC and cellular differentiation.